PENGGUNAAN BUDAYA KOREA SELATAN DALAM UPAYA PEMASARAN PRODUK SUSU MUJIGAE UNTUK MENDORONG KEPUTUSAN PEMBELIAN KONSUMEN DI SURABAYA - Axel Sutanto; Ferrinadewi, Erna (Universitas Widya Kartika Surabaya, 2024)
This research aims to analyze the influence of South Korean cultural trends (Hallyu) on sales of Mujigae products in Surabaya. The Hallyu phenomenon, which includes Korean music, drama and food, has become a global trend that influences many aspects of life, including consumer preferences. In a marketing context, Korean culture is often used as a tool to attract consumer interest and encourage purchasing decisions.The research method used is a combination of qualitative approaches. In order to be able to explore the meaning of events or phenomena that appear to be the impact of South Korean cultural trends on consumer purchasing decisions for Mujigae products and also to obtain specific, in-depth and transparent data from the results of consumer interviews. Data analysis was carried out using Narrative Analysis techniques to get to know consumers more deeply and their perspectives on Mujigae products.The research results show that elements of Korean culture such as the influence of trends generated by K-pop celebrities, packaging design, and marketing campaign themes significantly increase consumer attention and interest in Mujigae products. Consumers, especially young ones, show a strong preference for products related to Korean culture. Apart from that, the use of social media has proven to be effective in increasing engagement and brand awareness. Hallyu trend has a positive impact on sales of Mujigae products in Surabaya. Marketing strategies that integrate elements of Korean culture can encourage consumer loyalty and increase sales volume. Therefore, companies are advised to continue to innovate and follow developments in Korean cultural trends and consider expanding research coverage to other large cities in Indonesia.